Dementia in Sub-Saharan Africa: tools, prevalence and risk factors - (:unkn) unknown (My University, 2010)
Given the ageing population worldwide and the consequent epidemiological transitions, dementia is now a major public health concern in developing countries. The burden of dementia implies human, social, and economical consequences. First estimates of dementia prevalence in developing countries reported low rates (<5%) contrasting with observations made in developed countries, ranging from 5 to 20%. Few studies have been carried out in Africa whereas african elderly population will dramatically increase by 2025.During this PhD thesis, we studied the different tools allowing to screen dementia in low income countries, where culture differences and illiteracy are important. The determination of age in epidemiological studies focused on neurodegenerative disorders like dementia is of great importance, so a method to estimate the age with historical landmarks was validated.Three population-based studies were carried out in french speaking african countries: in Djidja (Benin), in Bangui (Central African Republic) and in Brazzaville (Congo), in order to estimate prevalence of dementia in elderly over 65 years and to study risk factors for this affection. By a door-to-door approach, these studies allowed to screen about 500 subjects in each study site with the Community Screening Interview for Dementia (CSI-D) and the Five Words Test. The prevalence of dementia was low in the rural area of Benin (2.6%), whereas it was higher in Central African cities (8.1% in Bangui and 6.7% in Brazzaville). Age and current depressive symptoms were the two factors most significantly associated with dementia in these populations. Surprisingly, the absence of schooling was never associated with dementia. The association between dementia and Lower-Extremities Peripheral Artery Disease (PAD) has particularly been explored in Central Africa, using the ankle-brachial index as a marker of PAD and general atherosclerosis. While the prevalence of PAD was high in elder population
Keywords: African Research